Mixture of MMP-2, MLC, and NOS Inhibitors Affects NO Metabolism and Protects Heart from Cardiac I/R Injury - Anna Krzywonos-Zawadzka; Aleksandra Franczak; Grzegorz Sawicki; Iwona Bil-Lula (Cardiology Research and Practice)
Objectives. Coronary reperfusion procedure leads to ischemia/reperfusion injury of the heart (IRI). IRI arises from increased degradation of myosin light chains and increased activity of matrix metalloproteinase 2 (MMP-2). Increased production of toxic peroxynitrite (ONOO−) during oxidative stress is a source of increased nitration/nitrosylation of contractile proteins, which enhance their degradation through MMP-2. Hence, an imbalance in nitric oxide (NO) metabolism along with oxidative stress is an important factor contributing to pathophysiology of cardiovascular disorders, including myocardial infarction. The aim of the current study was to provide an important insight into understanding the interaction of iNOS, eNOS, and ADMA during oxidative stress and to propose the beneficial therapy to modulate this interaction. Material and Methods. Pathogen-free Wistar rats were used in this study as a surrogate heart model ex vivo. Rat hearts perfused using the Langendorff method were subjected to global no-flow ischemia with or without administration of DOXY (1 µM), ML-7 (0.5 µM), and L-NAME (2 µM) mixture. Haemodynamic parameters of heart function, markers of I/R injury, tissue expression of iNOS, eNOS, and phospho-eNOS, asymmetric dimethylarginine, and NO production as well as MMP-2 activity were measured. Results. Mechanical heart function and coronary flow (CF) were decreased in the hearts subjected to I/R. Treatment of the hearts with the tested mixture resulted in a recovery of mechanical function due to decreased activity of MMP‐2. An infusion of Doxy, ML-7, and L-NAME mixture into I/R hearts decreased the expression of iNOS, eNOS, and phospho-eNOS and in consequence reduced ADMA expression. Decreased ADMA production led to enhanced NO synthesis and improvement of cardiac function at 85% of aerobic control. Conclusions. Synergistic effect of the multidrug therapy with the subthreshold doses allows addressing a few pathways of I/R injury simultaneously to achieve protection of cardiac function during I/R.